Ethical-Spiritual Dimensions of 21st-Century Education: Taming Artificial Intelligence with Human Intelligence - Muhammad Yaumi (Madrasah Tsanawiyah DDI Cilellang, 2024)
Intellectual intelligence and multiple intelligences have produced very sophisticated artificial intelligence. The progress of the artificial intelligence sector has implications for an educational paradigm that prioritizes cognition so that the ethical-spiritual dimension of education is increasingly eroded. This study aims to analyze the importance of developing heart education (human intelligence) in 21st-century education. The discussions in this literature study are focused on human intelligence, artificial intelligence, and the ethical-spiritual dimension of 21st-century education. Documented data from books, journals, and articles was then analyzed using content analysis techniques. The results show that artificial intelligence is developed in a value-free and uncontrolled manner. The impact is an increase in the number of unemployed (job automation), privacy violations, and even weapons automation. This must be controlled from an early age, both through collective awareness of ethical-spiritual values and through the development of humane, dignified, and spiritual artificial intelligence creativity. This research has implications for the importance of developing the ethical-spiritual dimension of 21st-century education, which not only fills the void in values in education but also helps educators, students, and other concerned parties find and know God.